DOI: 10.32469/10355/60423
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and efficiency characteristics of an inlet metering valve controlled fixed displacement pump

Abstract: This project developed the inlet metering system. An inlet metering system represents a new option in hydraulic pump design. Traditional pressure controlled hydraulic pumps rely on either swashplate displacement (for variable displacement pumps) or bleed off valves (for fixed displacement pumps). Variable displacement pumps require mechanically complex parts which are expensive to machine and prone to break down. Bleed off valves represent a significant loss in system efficiency. In contrast, the inlet meterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…There has also been more recent research on the subject. In 2016, Wisch presented his PhD thesis, which focuses on the dynamics and efficiency of an inlet-metered pump [97]. The following year, Ali presented his PhD thesis [5] on efficiency and system implementation.…”
Section: Inlet Meteringmentioning
confidence: 99%
See 1 more Smart Citation
“…There has also been more recent research on the subject. In 2016, Wisch presented his PhD thesis, which focuses on the dynamics and efficiency of an inlet-metered pump [97]. The following year, Ali presented his PhD thesis [5] on efficiency and system implementation.…”
Section: Inlet Meteringmentioning
confidence: 99%
“…It has been shown that the efficiency could be increased with a reduced switching frequency, but at the cost of less smooth control. Regarding inlet metering, it has not achieved very satisfactory efficiencies in practice, but that is partly explained by the pumps that have been used [97]. Part-bypass can be efficient if the pressure drops over the valves are small and if the machines have small losses at low pressure levels.…”
Section: Efficiencymentioning
confidence: 99%